Transparency in Public Service Governance: A Case Study about Identification Card Service Transparency in Merjosari, Lowokwaru, Malang (Journal of Governance and Development (JGD), 2016)
Study entitled â€œTransparency in Public Service Governance: a Case Study about Identification Card Service Transparencyâ€ is categorized as a case study. The setting of a study is an area called â€œMerjosariâ€ located in Lowokwaru region in Malang, East Java. The data collection methods are in-depth interview and documentary. The data analysis technique is descriptive qualitative. Based on the result of the data analysis, transparency in Identification card service in Malang, more particularly any service related to electronic Identification card, has run relatively well. However, there has yet been comprehensive, valid and up-to-date information about Identification card service. As an example, there is not any information about electronic Identification card and conflicting information about how long it takes for issuing new Identification card. Implementation of modern information technology (IT) especially the internet network in public service governance (Identification card service) is limited to storing information in the computers. As the consequence, the internet network and the modern devices as the facilities to aid the Identification card service are considered as waste of resources by the government or the public. In order to develop and maintain transparency, the use of internet network and modern IT devices/ softwares should be encouraged in order to create centralized e-service for the sake of active citizen of change in public service governance. Therefore, active participation from the government officers and the public in making use of the modern technology for public service governance is urgently needed in the future.